Фантазеры: [рассказы : для младшего школьного возраста] / Н. Носов - Носов Николай Николаевич (ЭКСМО, 2014)
Экземпляры: ф.15 (20210225) / Инвентарный номер: 60669 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Н 84 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44